Six Species of Epiphytic Algae Phycopeltis Millardet (Trentepohliaceae, Chlorophyta) Collected from Royal Belum Rainforest, Perak, Malaysia - Fatin Fadhilah Mohd Kamaruddin; Hideyuki Nagao (Tropical Life Sciences Research, 2019)
Algae are commonly referred as the aquatic algae and the existence of the terrestrial green algae is less portrayed. Trentepohliales is an order of filamentous green algae living terrestrially. These algae can be parasitic, epiphytic or free living organism. They are frequently found on parts of tropical plants and rocks. However, research regarding these organisms is still limited especially in Malaysia. Hence, the objectives of this study were to survey the distribution of the epiphytic green algae (Phycopeltis Millardet) on plant leaves in Royal Belum Rainforest, Perak and to recognise the genus and species of the algae. Leaves of forest plants (mainly shrubs) with green or brownish orange spots were collected and examined. Identification of the genus and species of the algae was done morphologically. In the present study, epiphytic green algae from the genus Phycopeltis were collected from 10 host plants. Among the identified species were P. amboinensis (Karsten) Printz, P. arundinacea (Mont.) de Toni, P. epiphyton Millardet, P. irregularis (Schmidle) Wille, P. flabellata R.H. Thompson & Wujek and P. treubii Karsten while P. amboinensis was the most common species. Pada kebiasaannya alga dirujuk sebagai alga yang hidup di dalam air dan kewujudan alga yang hidup di darat kurang diperkatakan. Trentepohliales adalah satu klasifikasi alga hijau berfilamen yang hidup di darat. Alga ini boleh menjadi parasit, epifit atau hidup tanpa perumah. Alga selalunya dijumpai di atas bahagian tumbuhan tropikal dan juga batu. Walau bagaimanapun, kajian berkenaan organisma ini masih terhad terutamanya di Malaysia. Oleh yang demikian, objektif kepada kajian ini adalah bagi meninjau taburan alga hijau epifit (Phycopeltis Millardet) pada daun tumbuhan di Hutan Simpan Royal Belum, Perak dan juga mengenal pasti genus dan spesis alga berkenaan. Daun tumbuhan hutan yang kebanyakannya tumbuhan semak dengan tompok hijau dan coklat kejinggaan telah dikutip dan diperiksa. Pengecaman bagi genus alga telah dilakukan berdasarkan morfologinya. Dalam kajian ini, alga hijau epifit daripada genus Phycopeltis telah dijumpai pada 10 tumbuhan perumah. Antara alga yang dikenal pasti termasuklah P. amboinensis (Karsten) Printz, P. arundinacea (Mont.) de Toni, P. epiphyton Millardet, P. irregularis (Schmidle) Wille, P. flabellata R.H. Thompson & Wujek dan P. treubii Karsten manakala P. amboinensis adalah spesis yang paling kerap ditemui.